Synthesizing the Organizational Factor with the Rule of Parent and Pediatric Nursing Behavior toward Hospital Performance: Evidence from Indonesia - Rusida Harjayanti Sanindya Arum; Ferdi Antonio (Jurnal Locus Penelitian dan Pengabdian, 2026)
This study examines the influence of organizational factors and parental engagement on pediatric nurse caring behavior and perceived hospital performance in Indonesian private hospitals. Despite global improvements in healthcare quality, challenges persist in maintaining high standards of nursing care, particularly in pediatrics, where parental involvement significantly affects patient outcomes. The research aims to identify how managerial support, nurse-nurse collaboration, doctor-nurse relationships, promotion of patient safety, and staffing/resources impact nurses’ caring behavior, mediated by parents’ education and involvement. A quantitative cross-sectional survey was conducted with 104 pediatric nurses from five private hospitals, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate reliability, validity, and hypothesized relationships. Results indicate that pediatric nurse caring behavior is primarily influenced by parental involvement, which is enhanced by the promotion of patient safety and parental education. Managerial support, nurse-nurse collaboration, and doctor-nurse relationships showed limited direct effects on parental engagement. The findings highlight that structural and process factors, such as resource allocation and patient safety initiatives, indirectly improve hospital performance through increased parental participation and nurse caring behavior. The study concludes that hospital management should prioritize strategies fostering parental involvement, support nurses’ caring practices, and promote patient safety to enhance both perceived hospital performance and overall quality of pediatric care.